Effect of music therapy on children with autism spectrum disorders in the Chinese population: a systematic review and meta-analysis - Yang, Yajing; Wang, Yu; Li, Wenhui; Su, Li (Frontiers in Psychiatry, 2025)
ObjectivesThis study aimed to investigate the efficacy of music therapy (MT) in children with autism spectrum disorder (ASD) in the Chinese population through a meta-analysis.DesignSystematic review and meta-analysis.SettingWe performed a systematic review according to the PRISMA guidelines. A systematic and comprehensive search was conducted across five databases: PubMed, Web of Science, Chinese Knowledge Infrastructure (CNKI), China Science and Technology Journal Database, and Wanfang Database, up to the end of September 2024, that administered MT to children with ASD. Continuous variables were reported as standardized mean differences (SMD) accompanied by 95% confidence intervals (CIs). All analyses were carried out using the Stata statistical software package version 16.0.ResultsTwenty-three studies were included in our meta-analysis. The results showed that MT significantly decreased the total ATEC (autism treatment evaluation checklist) score (SMD = -2.52, 95% CI: -3.69 ~ -1.35, P < 0.001), ABC (autism behavior checklist) (SMD = -1.07, 95% CI: -1.52 ~ -0.61, P < 0.001), and CARS (childhood autism rating scale) score (SMD = -1.50, 95% CI: -2.26 ~ -0.74, P < 0.001). Specifically, MT significantly improved communication skills (SMD = -1.10, 95% CI: -1.54 ~ -0.66, P < 0.001), social interaction skills (SMD = -1.69, 95% CI: -2.59 ~ -0.78, P < 0.001), language ability (SMD = -1.15, 95% CI: -1.56 ~ -0.74, P < 0.001), and cognitive function (SMD = -1.80, 95% CI: -2.73 ~ -0.87, P < 0.001) compared to the control group.ConclusionMT can improve communication skills, social interaction skills, language ability, and cognitive function in children with ASD disorders in the Chinese population.